POLITIK HUKUM ISLAM ERA KESULTANAN - - Syifa; Nabila Saifin Nuha Nurul Haq (Institut Dirosat Islamiyah Al-Amien Prenduan, 2017)
The existence of Islamic law is often influenced by political conditions and the authorities. In Indonesia, Islamic law is still enforced half-heartedly. Whereas, in the sociological and cultural level, Islamic law is the implemented law of Muslim society who live in Indonesia. This can be seen in the history of the kingdoms in Indonesia who applied Islamic law in their policies. Based on the phenomenon, this paper examines the politics of Islamic law during the Sultanate in Indonesia, with description of some IslamicKingdoms in Indonesia and how the Kingdoms implement the Islamic law as well as legal materials that have been impose on the Kingdoms.The results of the studyfind out that the politics of Islamic law during the Sultanate are concluded in the form of the following policies: making Islam as the official religion of Kingdom, the appointment of some positions in the Kingdom's authorities in the field of religion, enforcementof several quasi-law handbooks that are based on Islamic Sharia to be used as guidance in the resolution of an issue, such as Papakeum in the Kingdom of Cirebon and book of Jugul Mudain the Kingdom of Demak.